Designing Accessible Maps on Mobile Devices for Blind and Visually Impaired Users - Calle-Jiménez, Tania (2020)
Currently, there is a high percentage of people with visual disabilities worldwide. Sometimes, these people do not have access to the information of online geographic maps. A traditional map published on the Web does not provide the necessary alternative information for people with visual disabilities. This research presents a mobile application with geographic maps that provides the information in audio format to blind and visually impaired users. The application uses the Scalable Vector Graphics (SVG Tiny) format that allows additional information to be stored within the map code. SVG Tiny provides to screen readers the content inside of map code to transform text to audio. The tests were carried out through accessibility assessment tools, which showed a level of accessibility greater than 90%. In addition, tests were carried out with blind people, who were satisfied with the level of accessibility of the mobile application. © 2020, The Editor(s) (if applicable) and The Author(s), under exclusive license to Springer Nature Switzerland AG.